GAG Builder: a web-tool for modeling 3D structures of glycosaminoglycans - Singh, Arunima (Glycobiology, 2019)
Here we report the launch of a web-tool (the GLYCAM-Web GAG Builder, www.glycam.org/gag) for the rapid and straightforward prediction of 3D structural models for glycosaminoglycans (GAGs). The tool provides the user with coordinate files (PDB format) for use in visualization, as well as files for performing MD simulation with the AMBER software package. Counter ions and water may also be added as desired. The tool is designed with the non-expert in mind, and as such has implemented typical default values for structural parameters, which the user may change if desired. Multiple GAG types are supported, including Heparin/Heparan Sulfate, Chondroitin Sulfate, Dermatan Sulfate, Keratan Sulfate, and Hyaluronan; however, the user may alter the default sulfation patterns to create novel sequences. The common non-natural unsaturated uronic acid (ΔUA) and its sulfated derivative are also supported.